Motivation and Social Relations in School Following a CBT Course for Adolescents With Depressive Symptoms: An Effectiveness Study. Issue 2 (3rd March 2016) - Garvik, Margit; Idsoe, Thormod; Bru, Edvin
Abstract : The present study aimed to investigate changes in school functioning, including motivation, intentions to quit school and social relations in school, following an early group based CBT intervention implemented for depressed adolescents. The "Adolescent Coping with Depression Course" (ACDC) is such an early group intervention. The primary target group in the present study was 16–20 years old adolescents with subclinical or mild-to-moderate depression. The research design implemented was a pre-post design. Results indicated a strong reduction in depressive symptoms among study participants according to Cohen's criteria, a small to medium improvement in perceived social relations in school, but no change in school motivation and intentions to quit school.